Political science on the internet a student's guide - Stull, Andrew T. (Prentice Hall, 1997)
This book is designed to add new dimensions to your learning experience. It will help you navigate your journey through cyberspace. Revolutionary and resourceful, it makes surfing the net simple - so get connected now and ride the wave of information's future!